Recombinant luteinizing hormone supplementation to recombinant follicle stimulating hormone therapy in gonadotropin releasing hormone analogue cycles: what is the evidence?. (4th May 2018) - Younis, Johnny S.; Laufer, Neri
Abstract: Objective: To look into current evidence exploring the added value of rLH supplementation to rFSH in GnRH analogues cycles, to identify groups of women that still have no evidence for adjuvant rLH therapy and to discuss ways that may advance research on this topic. Methods: Eight systematic reviews and meta-analyses exploring the benefit for pregnancy achievement of rLH supplementation, excluding other LH activity preparations, to GnRH analogues cycles in the ART setting were thoroughly evaluated. Results: Evidence exists to show that rLH supplementation seems to have added value for pregnancy achievement in women with poor ovarian response and in women ≥35 years of age employing the GnRH agonist protocol, while the evidence is still debatable when the GnRH antagonist is administered. In the general infertile population, rLH supplementation does not have added value in the GnRH-antagonist cycles while the evidence is still controversial when the GnRH agonist is employed. Whether rLH supplementation may have a benefit in some young, normo-gonadotropic women, who may develop LH deficiency following GnRH analogues, is still to be shown. The main task remains how to identify subgroups of women that may benefit from rLH supplementation. Conclusion: An accurate definition of the LH threshold in GnRH analogue treated cycles may contribute to the discussion of which subgroups of women may benefit from adjuvant rLH therapy.